Advances in Mechanical Design c - Tan, Jianrong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focus on innovation, main objectives are to bring the community of researchers in the fields of mechanical design together; to exchange and discuss the most recent investigations, challenging problems and new trends; and to encourage the wider implementation of the advanced design technologies and tools in the world, particularly throughout China. The theme of 2021 ICMD is (3z(BInterdisciplinary and Design Innovation(3y (Band this conference is expected to provide an excellent forum for cross-fertilization of ideas so that more general, intelligent, robust and computationally economical mechanical design methods are created for multi-disciplinary applications.s
Chapter 1: Digital Rolling Test of Cycloidal Hypoid Gears Based on Measuring Tooth Surface Data -- Chapter 2: Dynamic and Experimental Study of Lathe Tool with High Damping Alloy Layer -- Chapter 3: Dynamic Behavior Research of Boring Cutter with High Damping Alloy Sleeve -- Chapter 5: Systematic Framework for Product Family Multi-agent Performance Evaluation and Optimization based on Configuration Design -- Chapter 6: Design and study of symmetrical two-fingered in-hand dexterous manipulation -- Chapter 7: Numerical Simulation and Experimental Verification of Oil-free Single Screw Air Compressor for Hydrogen Fuel Cell -- Chapter 8: An Elastoplastic Contact Model Considering Wear Based on Digital Rough Surfaces in Spatial Domain -- Chapter 9: A Novel Approach for Identifying Electromagnetic space-time Coupling Load of Wind Turbine -- Chapter 10: Research on a RSM based parameter optimization method and its application in mandible reconstruction implant.
Keywords: Engineering design; Control engineering; Robotics; Automation; Industrial engineering; Production engineering; Technological innovations; Engineering Design; Control, Robotics, Automation; Industrial and Production Engineering; Innovation and Technology Management; Industrial design -- Congresses; Product design -- Congresses